Respon Awal Petani, Nelayan, dan Usaha Mikro, Terhadap Bantuan COVID-19: (Initial Responseof Farmers, Fishers, and Micro-enterprises toward COVID-19 Recovery Funds) - Crisanty Sutristyaningtyas Titik; Ris Yuwono Yudo Nugroho (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
In general, research proposes to assess the Covid-19 Response Program's implementation based on the receiver community's perceptions. A qualitative approach is used to study and interpret the meaning of an individual or group of people. Respondents were selected purposively in three districts in East Java, namely Lamongan, Bangkalan, and Gresik. The following is a brief conclusion that: (1) initial information is clear enough; thus, the process of obtaining assistance is simple, and the requirements that must be met are also pleased, (2) implementation of pandemic response assistance has been running, and social service has been running before, and (3) impact of the pandemic community income depends on the type of business, its scale, and its strategic capabilities. Initial indications that the micro-business sector is more vulnerable to the impact of the pandemic